Investigation of Plasmids Among Clinical Staphylococcus aureus and Staphylococcus haemolyticus Isolates From Egypt - Mores, Carine R.; Montelongo, Cesar; Putonti, Catherine; Wolfe, Alan J.; Abouelfetouh, Alaa (Frontiers in Microbiology, 2021)
Staphylococci can cause a wide array of infections that can be life threatening. These infections become more deadly when the isolates are antibiotic resistant and thus harder to treat. Many resistance determinants are plasmid-mediated; however, staphylococcal plasmids have not yet been fully characterized. In particular, plasmids and their contributions to antibiotic resistance have not been investigated within the Arab states, where antibiotic use is not universally regulated. Here, we characterized the putative plasmid content among 56 Staphylococcus aureus and 10 Staphylococcus haemolyticus clinical isolates from Alexandria, Egypt. Putative plasmid sequences were detected in over half of our collection. In total, we identified 72 putative plasmid sequences in 27 S. aureus and 1 S. haemolyticus isolates. While these isolates typically carried 1 or 2 plasmids, we identified one isolate – S. aureus AA53 – with 11 putative plasmids. The plasmid sequences most frequently encoded a Rep_1, RepL, or PriCT_1 type replication protein. As expected, antibiotic resistance genes were widespread among the identified plasmid sequences. Related plasmids were identified amongst our clinical isolates; homologous plasmids present in multiple isolates clustered into 11 groups based upon sequence similarity. Plasmids from the same cluster often shared antibiotic resistance genes, including blaZ, which is associated with β-lactam resistance. Our analyses suggest that plasmids are a key factor in the pathology and epidemiology of S. aureus in Egypt. A better characterization of plasmids and the role they contribute to the success of Staphylococci as pathogens will guide the design of effective control strategies to limit their spread.